2012
DOI: 10.1029/2011ja017415
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale current systems and ground magnetic disturbance during deep substorm injections

Abstract: [1] We present a detailed analysis of the large-scale current systems and their effects on the ground magnetic field disturbance for an idealized substorm event simulated with the equilibrium version of the Rice Convection Model. The objective of this study is to evaluate how well the bubble-injection picture can account for some classic features of the substorm expansion phase. The entropy depletion inside the bubble is intentionally designed to be so severe that it can penetrate deep into geosynchronous orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 62 publications
10
110
0
Order By: Relevance
“…The BBFs in the braking phase are expected to add to the partial ring current and contribute to strengthening the R2 FAC and the ionospheric Pedersen current closure in the ionosphere (and thereby enhancing the EEJ) in Harang region-south, as we document in our ground-satellite observations at dusk. The magnetospheric part of this phenomenon has been predicted by Yang et al (2012) and Birn and Hesse (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BBFs in the braking phase are expected to add to the partial ring current and contribute to strengthening the R2 FAC and the ionospheric Pedersen current closure in the ionosphere (and thereby enhancing the EEJ) in Harang region-south, as we document in our ground-satellite observations at dusk. The magnetospheric part of this phenomenon has been predicted by Yang et al (2012) and Birn and Hesse (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Henderson et al, 2006, andBurke et al, 2007). According to the modeling work of Yang et al (2012) and Birn and Hesse (2013) and the experimental study of Frissell et al (2011) such deep inward penetration of the plasma-depleted flux tubes may contribute to the partial ring current and associated R2 FAC coupling to the ionosphere. In MHD studies it has been shown that shears in the azimuthal flows near the plasma sheet-partial ring current interface can give rise to R1 and R2 polarity FACs at the outer and inner edges of the intruding plasma bubbles (Birn and Hesse, 2013).…”
Section: P E Sandholt Et Al: Repetitive Substorm Activity Driven Bmentioning
confidence: 99%
“…The role of Earthward-propagating dipolarisation front flow bursts within X = −20 to −10 R E as a basic element (substructure) in the substorm process in the magnetotail is emphasized by Lyons et al (2012). On the association between dipolarization of flux tubes, inward transport of flux from the tail, and the generation of twin-cell flow in the ionosphere we refer to the review paper by Cowley (2000) and the recent simulation results of Yang et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Rice Convection Model (RCM) and the Rice Convection Model-Equilibrium (RCM-E) have been extensively used to investigate how the plasma inside depleted flux tubes is transported in the nearEarth region [Lemon et al, 2004;Zhang et al, 2008;Zhang et al, 2009aZhang et al, , 2009bYang et al, 2008Yang et al, , 2011Yang et al, , 2012Yang et al, , 2014aYang et al, , 2014b. The model uses the slow-flow approximation and assumes an isotropic pressure distribution along magnetic field lines.…”
Section: Introductionmentioning
confidence: 99%